Resection and Surgically Targeted Radiation Therapy for Initial or Salvage Treatment of Aggressive Meningioma: Results From a Prospective Trial. (16th November 2020) - Rogers, Leland; Nakaji, Peter; Youssef, Emad; Smith, Kris; Zabramski, Joseph M; Thomas, Terry; Dardis, Christopher; Pinnaduwage, Dilini; Brachman, David
Abstract: INTRODUCTION: For aggressive and/or recurrent meningiomas achieving durable local control (LC) remains problematic. Resection (R) alone is typically insufficient and even with the addition of radiation therapy (RT) LC is suboptimal in many series. METHODS: From 2/2013-2/2018 recurrent and newly diagnosed aggressive meningiomas were treated on a single arm, multi-histology study (ClinicalTrials.gov, NCT#03088579). Intraoperatively the tumor bed was lined with collagen tiles imbedded with Cs-131, delivering 60–80 Gy at 5 mm depth. No additional local therapy was given absent progression. RESULTS: 35 meningiomas in 28 patients were treated; 29 were recurrent and 6 had no prior therapy. WHO grade was I in 2 patients, II in 28, and III in 5. In the 29 recurrent cases, 22 had prior R+RT, 6 R only, and 1 RT only. For recurrent tumors, mean prior same site surgeries was 2 (range 0–5), and mean prior RT courses 1.7 (range 0–3). Median age was 66 years (range 37–82), KPS 80 (70-100), female: male ratio 15:13. Mean time for implantation was 5 minutes. For all tumors, at a median radiographic follow-up of 25.5 months (range 0.1-71) treatment site progression occurred in 20% (7/35) and median time to progression had not been reached (95% CI > 35.6 months). Overall LC at 12/24/36/48 months was 100/89/72/72% for all tumors, 100/93/79/79% for Grade II, and 100/50/0/0% for Grade III, respectively. No patient who received CTBT as their initial radiation treatment has failed.Median overall survival was 50 months. Four symptomatic adverse events occurred, 2 wound breakdowns requiring surgery and 2 radiation-related brain changes, medically treated. CONCLUSION: R+CTBT demonstrates favorable safety and LC outcomes in this single-arm prospective trial that includes heavily pre-treated patients. A commercial version of the device recently received FDA clearance for use in newly diagnosed malignant or recurrent intracranial neoplasms including meningiomas.